The Contribution of Local Government Finance to the Islamic Human Development Index - Hergastyasmawan, Angga; Ahyar, Muhammad Khozin; Irianto, Ellen D Oktanti (MultiTech Publisher, 2024)
This research aims to analyze the Islamic Human Development Index (IHDI) scores in East Kalimantan Province for the period 2017-2022 and investigate the impact of the Regional Revenue and Expenditure Budget (APBD) in the fields of education, health, and the economy on IHDI and its dimensions (Ad-Dien, Al-'Aql, An-Nafs, An-Nasl, and Al-Maal). This research method is quantitative descriptive, involving the calculation of IHDI scores and its forming indices using appropriate formulas. Hypothesis testing is conducted through simple linear regression analysis. The research results indicate that the IHDI in East Kalimantan Province is generally categorized as a high level of human development, despite experiencing fluctuations with a predominance of improvement. Specifically, the APBD has an influence on the IHDI score, with education spending affecting the Index of Ad-Dien and Al-'Aql, health spending affecting the Index of An-Nafs and An-Nasl, and economic spending affecting the Index of Al-Maal